Sunscreen Formulation Type and Melasma Severity: A Cross-Sectional mMASI-Based Study in Indonesian Women - Yuli Wahyu Rahmawati; Mita Permatasari Araminta; Musa Ghufron; Muhammad Perdana Airlangga; Salsabil Khalizah Ramadhan; Ridha Ramadina Widiatma (Phlox Institute: Indonesian Medical Research Organization, 2025)
Background: Melasma is a common acquired hyperpigmentation predominating in women of Fitzpatrick phototype III–V, in whom ultraviolet and visible light are central drivers. Because organic (chemical) filters attenuate visible light poorly relative to inorganic (physical) filters, sunscreen formulation type may influence severity, yet real-world Indonesian evidence is limited. Objective: To determine the association between sunscreen type and melasma severity. Methods: In this STROBE-compliant analytic cross-sectional study, 30 consecutive adult women with clinically diagnosed melasma were enrolled at RSUD Dr. Soegiri Lamongan, East Java (October 2023–January 2024), in collaboration with Universitas Muhammadiyah Surabaya and Universitas Brawijaya. Severity was graded with the modified Melasma Area and Severity Index (mMASI, 0–24) after Wood-lamp subtyping and Fitzpatrick phototyping. Associations were tested with chi-square, contingency coefficient, Cramér's V, odds ratios, and exploratory logistic and ROC analyses. Results: Moderate–severe melasma affected 70.0% (95% CI 52.1–83.3); physical sunscreen was most frequent (63.3%). Sunscreen type was significantly associated with mMASI severity (χ² = 14.24, df = 4, p = 0.007; C = 0.567; Cramér's V = 0.487), physical users showing the lowest mean mMASI (9.9 ± 3.8). Reapplication was independently protective (adjusted OR 6.48, 95% CI 1.19–35.2, p = 0.031; composite AUC 0.79, 95% CI 0.62–0.95). Conclusion: Physical, visible-light-blocking sunscreens and consistent reapplication are associated with milder melasma, supporting broad-spectrum inorganic photoprotection as a first-line, low-cost intervention for Indonesian women.